Choice over Payment Schemes and Worker Effort - Martin Abel; Rulof Burger (Institute of Labor Economics (IZA), 2022)
We study the effect of monetary incentives on effort in a prosocial task: writing letters encouraging voter turnout. Volunteers are randomized to receive no incentive, unconditional upfront payment, payment conditional on completing the task, or to have a choice between the two payment schemes. The unconditional and conditional payment both increase task completion rates by about 18 percentage points (43%). Giving people a choice between the payment scheme doubles the effect on task completion (35 p.p., 84%). Unlike unconditional payments, a choice over contracts also increases time spent on the task and letter quality. Survey responses suggest that giving people a choice is effective because it increases task ownership rather than the desire to return a favor or avoid feelings of guilt.
Keywords: D86; D91; J22; 330; self determination; gift exchange; guilt aversion; labor supply